Update on Outcome Measure Development for Large Vessel Vasculitis: Report from OMERACT 12 - ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER (J RHEUMATOL PUBL CO, 2015)
Objective. The rarity of large vessel vasculitis (LVV) is a major factor limiting randomized controlled trials in LVV, resulting in treatment choices in these diseases that are guided mainly by observational studies and expert opinion. Further complicating trials in LVV is the absence of validated and meaningful outcome measures. The Outcome Measures in Rheumatology (OMERACT) vasculitis working group initiated the Large Vessel Vasculitis task force in 2009 to develop data-driven, validated outcome tools for clinical investigation in LVV. This report summarizes the progress that has been made on a disease activity assessment tool and patient-reported outcomes in LVV as well as the group's research agenda. Methods. The OMERACT LVV task force brought an international group of investigators and patient research partners together to work collaboratively on developing outcome tools. The group initially focused on disease activity assessment tools in LVV. Following a systematic literature review, an international Delphi exercise was conducted to obtain expert opinion on principles and domains for disease assessment. The OMERACT vasculitis working group's LVV task force is also conducting qualitative research with patients, including interviews, focus groups, and engaging patients as research partners, all to ensure that the approach to disease assessment includes measures of patients' perspectives and that patients have input into the research agenda and process. Results. The preliminary results of both the Delphi exercise and the qualitative interviews were discussed at the OMERACT 12 (2014) meeting and the completion of the analyses will produce an initial set of domains and instruments to form the basis of next steps in the research agenda. Conclusion. The research agenda continues to evolve, with the ultimate goal of developing an OMERACT-endorsed core set of outcome measures for use in clinical trials of LVV.
Keywords: VASCULITIS; TAKAYASU ARTERITIS; GIANT CELL ARTERITIS; LARGE VESSEL; OUTCOMES; QUALITY-OF-LIFE; GIANT-CELL ARTERITIS; TAKAYASUS-ARTERITIS; DISEASE; HEALTH; PERSPECTIVE; FILTER